Robots in agriculture – A case-based discussion of ethical concerns on job loss, responsibility, and data control - Sune Holm; Søren Marcus Pedersen; Tseganesh Wubale Tamirat (Smart Agricultural Technology)
There is a growing interest in using robots in agriculture due to increasing challenges of labour scarcity and cost. Field robots are expected to help overcome these challenges and to contribute to financial, environmental and social sustainability. However, socially responsible introduction of field crop robots will require awareness and consideration of ethical trade-offs by stakeholders including farmers, regulators, and manufacturers. In this article we discuss the ethical themes of job loss, moral responsibility, and data control in light of the results of sixteen interviews with key stakeholders conducted in 2022 under a European research project named Robs4crops.